2015
DOI: 10.3168/jds.2014-8984
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for the prediction of conception success to a given insemination in lactating dairy cows

Abstract: The ability to accurately predict the conception outcome for a future mating would be of considerable benefit for producers in deciding what mating plan (i.e., expensive semen or less expensive semen) to implement for a given cow. The objective of the present study was to use herd- and cow-level factors to predict the likelihood of conception success to a given insemination (i.e., conception outcome not including embryo loss); of particular interest in the present study was the usefulness of milk mid-infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 26 publications
7
68
4
Order By: Relevance
“…Recent studies from our group examining the genetic merit for fertility traits have reported greater DMI and BCS, superior metabolic status and uterine health (Cummins et al, 2012a;Moore et al, 2014a;Moran et al, 2017), earlier resumption of ovarian cyclicity, and greater luteal phase circulating concentrations of progesterone (Cummins et al, 2012b;Moore et al, 2014b) in cows with good genetic merit for fertility traits compared with cows with poor genetic merit for fertility traits. The results arising from this study highlight the strong associations between fertility subindex and PTA for both calving interval and survival with reproductive performance, in agreement with Fenlon et al (2017) and Hempstalk et al (2015). This highlights the importance of selecting for fertility traits and long-term gains that can be achieved in herd phenotypic reproductive performance.…”
Section: Pta and Fertility Subindexsupporting
confidence: 72%
“…Recent studies from our group examining the genetic merit for fertility traits have reported greater DMI and BCS, superior metabolic status and uterine health (Cummins et al, 2012a;Moore et al, 2014a;Moran et al, 2017), earlier resumption of ovarian cyclicity, and greater luteal phase circulating concentrations of progesterone (Cummins et al, 2012b;Moore et al, 2014b) in cows with good genetic merit for fertility traits compared with cows with poor genetic merit for fertility traits. The results arising from this study highlight the strong associations between fertility subindex and PTA for both calving interval and survival with reproductive performance, in agreement with Fenlon et al (2017) and Hempstalk et al (2015). This highlights the importance of selecting for fertility traits and long-term gains that can be achieved in herd phenotypic reproductive performance.…”
Section: Pta and Fertility Subindexsupporting
confidence: 72%
“…For example, sexed or premium bull semen could be used for cows predicted to have a high likelihood of conception, whereas cows with predicted poor fertility could be mated using semen from beef bulls, multiple doses, or semen from bulls of known high genetic merit for fertility. To our knowledge, Grzesiak et al (2010), Shahinfar et al (2014), and Hempstalk et al (2015) are the only authors who have reported the ability of some on-farm data to predict likelihood of conception to a given insemination of dairy cows. The value of the prediction accuracy ranged between 0.66 (Hempstalk et al, 2015) and 0.91 (Grzesiak et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, Grzesiak et al (2010), Shahinfar et al (2014), and Hempstalk et al (2015) are the only authors who have reported the ability of some on-farm data to predict likelihood of conception to a given insemination of dairy cows. The value of the prediction accuracy ranged between 0.66 (Hempstalk et al, 2015) and 0.91 (Grzesiak et al, 2010). Unfortunately, some of the important variables used in these studies might be difficult to obtain on-farm (e.g., BCS and BW) or cannot be predicted a priori (e.g., year).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on FT-MIR spectra to build equations predicting technological properties of milk such as milk acidity ), ability to coagulate, firmness of curd, or cheese yield (Dal Zotto et al, 2008;Colinet et al, 2015). Recent work has directly considered the FT-MIR spectrum of milk as a reflection of cows' status, with FT-MIR equations being developed to predict methane emissions of dairy cows (Dehareng et al, 2012;Vanlierde et al, 2016), likelihood of conception (Hempstalk et al, 2015), body energy status , energy intake and efficiency (McParland et al, 2014). In the work of LainĂ© et al (2017), the spectrum is even considered as a response for which the effect of pregnancy is evaluated.…”
Section: Introductionmentioning
confidence: 99%